Zes eeuwen klokkencultuur in de abdij van Averbode: Circa 1385 tot heden - Osta, Jozef van (Averbode Abdij Averbode, 2023)
On the initiative of the fellow brothers " buitenheren", a new bell was cast for the Averbode abbey tower in the jubilee year of the Premonstratensian order (1121-2021). It was named Hugo and refers to Blessed Hugo of Fosses, first abbot of Prémontré. This event prompted fellow brother Jozef Van Osta to describe chronologically and extensively the history of the bell and carillon culture of Averbode Abbey. As early as the 14th and 15th centuries, traces of bells and primes can be found in the abbey's rich archives. Throughout the centuries, eminent bell founders such as brothers Willem and Jasper Moer, François Hemony and Andreas Jozef Vanden Gheyn received commissions for the abbey. The book refers to clock inscriptions written by Erasmus of Rotterdam especially for Averbode. The turbulent history of the bells during the French period, the Second World War and the period afterwards receives ample attention. The abbey archives also recently discovered a manuscript from the 15th century with the rite for a bell dedication. A rare document with numerous regional variants. In short, this book is about bells and carillon and about people who bought and cherished them. This historiographical work was richly illustrated and published in a beautifully bound book. A real asset not only for the lover of bells and carillons, but for every bibliophile reader. (Translated with Deepl.com)
Keywords: Abdij van Averbode; History; Bell; Carillon; Averbode (Belgium)